The Right of Appeal under Section 35 of the Arbitration Act of Kenya: A Critique of the Supreme Court Decision in Nyutu Agrovet v Airtel Networks Limited (2019) eKLR - Sebayiga, Vianney (Strathmore Law Review, 2021)
An arbitral award is final and binding on the parties but may be set aside for failure to adhere to due process requirements. Section 35 of the Arbitration Act (Act hereafter) provides grounds for setting aside an arbitral award. It does not state whether decisions of the High Court on setting aside an arbitral award are final and thus cannot be appealed. In Nyutu Agrovet Limited v Airtel Networks Limited, the Supreme Court interpreted Section 35 to allow appeals on High Court decisions of setting aside an arbitral award. This paper analyses the Supreme Court decision and finds that it abrogated the internationally recognised arbitration principles such as party autonomy, the finality of arbitral awards and limited court intervention. Additionally, the paper discusses the implications of the decision on arbitral practice in Kenya. Using literature review and comparative jurisprudence, it advances that Section 35 does not allow appeals on decisions of the High Court. To this end, it proposes better interpretation techniques to safeguard the sanctity of arbitral awards.